Training for power and speed: Effects of increasing or decreasing jump squat velocity in elite young soccer players - Loturco, I.; Nakamura, F. Y.; Kobal, R.; Gil, S.; Cal Abad, C. C.; Cuniyochi, R.; Pereira, L. A.; Roschel, H. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to test the effects of 2 different velocity-oriented power training regimens by either increasing or decreasing the jump squat velocity during jump training sessions applied 3 times a week for 6 weeks in soccer players. Twenty-four elite under-20 soccer players were randomly assigned to an increased bar velocity group (IVG) or a reduced bar velocity group (RVG). Athletes had their countermovement jump heights, mean propulsive velocities (MPVs) in jump squat, leg press maximum dynamic strength (1 repetition maximum [RM]), 20-m sprint times, and zig-zag change of direction (COD) abilities assessed before and after the intervention. Performance in all tests improved after training in both groups. However, greater gains in 1RM and MPV using 50-90% of body mass (BM) were noted for the RVG. The IVG demonstrated greater improvements in speed at 5, 10, and 20 m and MPV with no additional external load and with 40% BM. Both groups improved similarly in countermovement jumps and COD. To conclude, both velocity-oriented power training regimens were effective in eliciting neuromechanical adaptations, leading to better strength/power/speed performances, and the choice as to the most suitable method should be tailored according to players' needs/deficiencies.